Peran Kode Etik Syariah dalam Memitigasi Resiko Fraud di Tengah Percepatan Digitalisasi Lembaga Keuangan Syariah Indonesia - Resky Amalia; Widia Natasya; Masyhuri, Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The digitization of Indonesian Islamic financial institutions presents opportunities for efficiency while increasing the risk of complex fraud. This study aims to analyze the role of the Sharia code of ethics in mitigating fraud risk in the era of digital transformation. The research method is descriptive qualitative with a literature study of previous research, official reports, and academic studies, which are analyzed to assess the effectiveness of the code of ethics as an instrument for fraud prevention. The results show that the internalization of Islamic codes of ethics through training, Sharia-based audits, and strengthening organizational culture significantly reduces the risk of internal and external irregularities. The integration of regulation, technology, and leadership supports the effectiveness of mitigation strategies, while customer education and digital monitoring strengthen service transparency. The Sharia code of ethics serves as a normative guideline and strategic instrument that can bring ethical, secure, and reliable governance to Sharia financial institutions. These findings emphasize the importance of a holistic approach to maintaining operational integrity amid the acceleration of digitalization.